Comparative evaluation of the blends of gas-to-liquid (GTL) fuels and biodiesels with diesel at high idling conditions: an in-depth analysis on engine performance and environment pollutants. Issue 17 (27th February 2015) - Hossain, S.; Masjuki, H. H.; Varman, M.; Kalam, M. A.; Rahman, S. M. Ashrafur
<x xml:space="preserve">Abstract</x> The effect of high-idling conditions at different engine performance-emission parameters were investigated using blends of GTL–diesel and biodiesel–diesel.